Poster 225: Accuracy of 3D Printed Cutting Guide Versus Free-hand Technique for Anterior Closing Wedge Proximal Tibia Osteotomy in an Animal Model. Issue 7 (30th July 2022) - Sanders, Justice; Garrone, Andrew; Geers, Katie; Binzel, Katherine; Siston, Robert; Knopp, Michael; Flanigan, David; Magnussen, Robert; Duerr, Robert
Objectives: Anterior closing wedge proximal tibia osteotomy (ACWPTO) is an effective treatment for patients with elevated posterior tibial slope (PTS) and recurrent anterior cruciate ligament (ACL) injuries. However, the preoperative planning and surgical execution can be challenging, especially with limited surgeon experience and training. The purpose of this study was to evaluate the initial design of a 3D printed patient-specific cutting guide (PSG) for performing ACWPTO in an animal model. It was hypothesized that the PSG for ACWPTO will more accurately achieve the desired PTS correction compared to a traditional free-hand (FH) technique. Methods: Thirty cadaveric porcine knees underwent lateral radiographs and computed tomography (CT) scans, and were randomly assigned to ACWPTO by PSG or FH technique. Three knees within each group were then assigned to a 10°, 12°, 14°, 16° or 18° correction. Knees assigned to the PSG group then underwent 3D modeling and a PSG was created in SolidWorks to complete the desired PTS correction (Figure 1). Knees assigned to the FH group were templated by an experienced orthopedic surgeon for performing ACWPTO by measuring a pre-determined wedge of bone to be removed from the anterior tibia. Surgeries were then performed by an experienced (attending physician), intermediate (resident physician), and novice surgeon (medical student). Each surgeon performed ACWPTO using the PSG and FH technique for each of the intended angles of correction (10°, 12°, 14°, 16°, 18°). Following ACWPTO, post-operative radiographs and CT scans were taken to measure the PTS and the accuracy was determined as the difference between the planned and actual PTS correction (Figure 2). The accuracy, surgical time, and radiation exposure were compared between surgeons using ANOVA. Further analyses to compare the variables of interest between the FH and PSG techniques were conducted using independent samples t-tests. Results: All data are summarized in Tables 1 and 2. Overall, we found the PSG to have significantly faster surgical time (6.4 +/- 2.2 minutes versus 12.0 +/- 3.9 minutes, p < 0.001) and less radiation exposure (8.7 +/- 4.9 mGy versus 58.7 +/- 28.1 mGy, p < 0.001). While the PSG trended towards increased accuracy with radiographic measurements of PTS, this did not reach statistical significance (1.6 +/- 1.6 degrees versus 2.9 +/- 2.0 degrees, p = 0.059). The highest accuracy was found for the resident (intermediate) surgeon using the PSG (0.5 +/- 0.5 degrees), which was significantly more accurate than FH technique for this surgeon (3.6 +/- 2.5 degrees, p = 0.026). Based on CT measurements of medial and lateral PTS we found the FH technique to be as accurate as the PSG (Table 2). Conclusions: One reason for the discrepancy between radiographic and CT measurements may be the lack of standardized methods for measuring PTS in porcine knees. The proximal tibia articular surface has a more complex geometry as compared to human knees, which did make measuring consistent landmarks challenging and is one of the primary limitations of this study. Other limitations of this study include the margin of error in the design of the 3D printed PSG, and accurate placement of the PSG on the proximal tibia. Guide placement was challenging if any cartilage remained around the tibial tubercle as this was not templated in the CT design. Also, PTS measurements can be highly dependent on limb rotation and observer experience. Despite these limitations, this study demonstrated the feasibility of a 3D printed PSG for performing ACWPTO in an animal model. This PSG was as accurate as the free-hand technique based on CT measurements and trended towards improved accuracy based on radiographic measurement of PTS. Future studies are planned to investigate this design in human cadaveric specimens. Table 1. Comparison of Results by Surgeon (Novice vs. Intermediate vs. Expert) Figure 1. A) 3D model of porcine tibia created in SolidWorks to create a patient specific cutting guide to perform anterior closing wedge tibial osteotomy. B) 3D printed patient specific cutting guide for anterior closing wedge tibial osteotomy. Table 2. Comparison of Results by Surgical Technique (Free-hand vs. Patient-Specific Guide) Figure 2. A) Pre-operative radiograph with measurement of posterior tibial slope. B) Post-operative radiograph after anterior closing wedge proximal tibial osteotomy performed with measurement of posterior tibial slope.